Current role of sentinel lymph node biopsy in the management of cutaneous melanoma: A UK consensus statement. Issue 1 (January 2020) - Peach, H.; Board, R.; Cook, M.; Corrie, P.; Ellis, S.; Geh, J.; King, P.; Laitung, G.; Larkin, J.; Marsden, J.; Middleton, M.; Moncrieff, M.; et al.
Summary: Sentinel node biopsy (SNB) has been at the forefront of the surgical staging of melanoma patients for the past 15 years. The high accuracy of this prognostic staging procedure is now recognised in all international guidelines for melanoma. However during this period there have been a number of important changes in the management of melanoma, many occurring within the past five years. The outcomes of five recent randomised Phase 3 trials have established the role of adjuvant targeted therapy and immunotherapy in resected Stage 3 and Stage 4 disease and have potentially changed the role of SNB. Two landmark international prospective studies have examined the benefit of performing a completion lymph node dissection (CLND) following the detection of microscopicallyinvolved sentinel nodes. Finally, the marked increase in the incidence of melanoma and the role of SNB in potentially guiding therapy has resulted in a significant increase in the pathological workload of the dermatopathology services. To address these issues a multi-disciplinary consensus meeting involving many melanoma experts from the UK was convened in May 2018. Three main areas were considered: oncology, surgery and pathology. This report is a summary of the conclusions reached, which were agreed by the clinicians attending the meeting and then externally peer reviewed. The recommendations summarised in this Consensus Statement.